2009
DOI: 10.1007/s00330-009-1405-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal 18F-FDG accumulation on PET without a corresponding CT abnormality is not an early indicator of cancer development

Abstract: Focal gastrointestinal 2-deoxy-2-[(18)F]-fluoro-D: -glucose (FDG) uptake can frequently be found on FDG-PET/CT even in patients without known gastrointestinal malignancy. The aim of this study was to evaluate whether increased gastrointestinal FDG uptake without CT correlate is an early indicator of patients developing gastrointestinal malignancies. A total of 1,006 patients without esophagogastric or anorectal malignancies underwent FDG-PET/CT. The esophagogastric junction, the stomach and the anorectum were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Heusner et al [4] evaluated esophagogastric FDG uptake in 546 patients without esophagogastric malignancies. They concluded that elevated esophagogastric FDG uptake does not predict cancer development and should not be investigated further if CT shows no unusual features.…”
Section: Physiological Fdg Uptake In Gastric Mucosamentioning
confidence: 99%
See 2 more Smart Citations
“…Heusner et al [4] evaluated esophagogastric FDG uptake in 546 patients without esophagogastric malignancies. They concluded that elevated esophagogastric FDG uptake does not predict cancer development and should not be investigated further if CT shows no unusual features.…”
Section: Physiological Fdg Uptake In Gastric Mucosamentioning
confidence: 99%
“…For gastric cancer screening, the usefulness of PET is limited because of physiological FDG uptake in the normal gastric wall and differences of FDG uptake according to the histological type of the tumor [1,2]. Physiological FDG deposits in the stomach may increase false-positive findings, although these deposits can be decreased by expanding the gastric wall by the patient consuming water or milk just before imaging acquisition [4,5]. As Koga et al [2] have reported, physiological gastric FDG uptake was shown to be significantly higher at the oral end; thus, strong gastric FDG uptake at the anal end suggested pathological uptake.…”
Section: Efficacy Of Pet For the Screening Of Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In general, such tracer accumulation is only faint or moderate and diffuse. Such a pattern is usually easy to identify as nonpathologic, especially if morphologic abnormalities are absent (2). However, there are still a considerable number of patients with a higher and more focal accumulation of 18 F-FDG in the intestine.…”
mentioning
confidence: 99%
“…In fact, the accumulation of 18 F-FDG in the distal oesophagus is not infrequent and Roedl et al [3] reported only 8.3% malignancy in incidental oesophageal 18 F-FDG uptake. Heusner et al [4] even postulated that an abnormal 18 F-FDG accumulation of the gastro-oesophageal junction does not need further investigation if there is no correlate on CT. Of course, in both of our presented cases, there was a mass on CT, justifying further investigation. In both cases, even after multiple biopsies were performed-although not advisable in leiomyomas-malignancy could not be confirmed.…”
Section: Discussionmentioning
confidence: 99%